Relational methods in logic, language and information - Blackburn, Patrick 1959-; Rijke, Maarten de; Venema, Yde (1995)
Abstract: "This paper discusses the use of relational methods in the interdisciplinary field of Logic, Language and Information. We first sketch the developments that lead up to the current focus on dynamics in the area. After that we give examples of logics of transition that natually arise in this setting, and we identify more general themes such as bisimulations, relativisations and dynamic modes of inference. We conclude with a discussion of newly emerging themes, and the limitations of the relational perspective."
Keywords: Grammatik; Grammar, Comparative and general; Logic, Symbolic and mathematical